Behavior of splice connection during transfer of vertical load in full-scale corner-supported modular building. (1st March 2021) - Lyu, Yi-Fan; Li, Guo-Qiang; Cao, Ke; Zhai, Si-Yuan; Li, Heng; Chen, Chen; Wang, Yuan-Zuo
Highlights: Full-scale corner-supported modular building was tested and simulated. Stages of connection behavior in transfer of vertical load was analyzed. Full-range variation of bolt pre-tension force in the bolt group was revealed. Tolerance of splice connection for extreme initial imperfections was studied. A transitional initial imperfection for modular building was found. Abstract: Splice connection, comprised of splice plates and slip-critical high strength bolts, is an efficient and convenient connecting technique for modular buildings. Previous investigations on this splice connection were mainly conducted based on tests of substructures, which may not reveal the real connection behavior in the whole modular building. To fill this research gap, this paper presents a comprehensive research on a full-scale corner-supported modular building assembled with splice connections. Behavior of the splice connection during the transfer of vertical load in the full-scale modular building is analyzed in details with combined experimental and numerical techniques. Test results showed that no unfavorable phenomenon was caused by the proposed splice connection before the global buckling of the module column. Based on the validated numerical model, a three-stage behavior during the entire loading process is found for the splice connection. The involvement of splice connection in the transfer of vertical load is negligible in the first stage while the splice connection provides sufficient constraint for the second-order moment at the bottom of module column in the second stage. The localized deformation and obvious formation of gap are found in the third stage. However, the analysis on the full-range bolt pre-tension force of the bolt group indicates that the origin of such negative phenomenon is located after the global buckling, which will not affect design on the vertical-load transfer performance of the module column. The sensitivity of connection behavior to the values of initial imperfections are also investigated by the parametric study. It is found that the proposed splice connection has a satisfactory tolerance for extreme initial imperfections. A transitional initial imperfection is further proposed, which may be used as an important reference for the practical control on the initial imperfection.